1970
DOI: 10.1073/pnas.65.3.564
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietic Activity of Steroid Metabolites in Mice

Abstract: Abstract. The per cent Fe59 incorporation into circulating erythrocytes as an indicator for new hemoglobin production was used in the polycythemic exhypoxic mouse system to study the effects of certain steroid hormone metabolites on erythropoiesis. Enhanced Fe59 incorporation was observed after the administration of several metabolites with a 5,3-H configuration, while those with a 5a-H configuration had no stimulatory effect. The stimulatory effect in avian systems has been shown by others to be due to an inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1971
1971
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…The side effects of this therapy, liver toxicity and virilization in females, justify temporary withdrawal of treatment, followed by a trial with another androgen, only in case of icterus. Concerning viriliza tion, experiments are now being carried out on new 5/9-H-steroid metab olites, devoided of virilizing effects, which will probably be used cur rently in clinical practice in a near future [10,11], Also, a small dose of glucocorticoids is generally associated to andro gen therapy [1,23,25]. The clinical results obtained in our patients do not seem to justify this treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The side effects of this therapy, liver toxicity and virilization in females, justify temporary withdrawal of treatment, followed by a trial with another androgen, only in case of icterus. Concerning viriliza tion, experiments are now being carried out on new 5/9-H-steroid metab olites, devoided of virilizing effects, which will probably be used cur rently in clinical practice in a near future [10,11], Also, a small dose of glucocorticoids is generally associated to andro gen therapy [1,23,25]. The clinical results obtained in our patients do not seem to justify this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the prolonged use of androgens, particularly of the new metabolites devoided of virilizing effects [10,11] and eventually bone marrow homotransplantation, made possible by the striking im provement in tissue typing techniques, appear to be the most promising therapeutic mean in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been recently shown that androgens increased 2,3-diphosphogIycerate in red cells of hemodialyzed patients, increasing the unloading of oxygen to the tissues [82]. Certain 5(3-H steroids are more active than other compounds [45,46]. Mirand et al [66] and Eschbach and Adamson [29] have found a minute increase in erythropoietin plasma level in some anephric patients after andro gen therapy.…”
Section: Treatmentmentioning
confidence: 99%
“…Plasma for ESF determination was also obtained from hyperoxic mice 1, 2, 3, and 4 days after two daily administrations each of 2.5 mg 19-ND dis solved in 0.1 ml of propylene glycol. Plasma ESF levels were measured in the post hypoxic polycythemic mouse system by injecting plasma samples of 0.5 or 1.0 ml each to mice on the 3rd and 5th hypoxic days, and 72 h radioiron incorporation was begun on the 6th posthypoxic day as previously described [19,23].…”
Section: Methodsmentioning
confidence: 99%